2017
DOI: 10.1016/j.conbuildmat.2017.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Properties and modification mechanisms of nano-zirconia filled reactive powder concrete

Abstract: The mechanical and electrical properties of reactive powder concrete (RPC) with nano-ZrO 2 (NZ) are investigated in this research. The reinforcing mechanisms of NZ to RPC are studied through thermogravimetry (TG) analysis, scanning electron microscope (SEM) observation and X-Ray powder diffraction (XRD) analysis. Research results indicate that the NZ has obvious modifying effect to RPC. The flexural, compressive and splitting strengths of RPC with NZ at curing age of 28 days achieve increases of 36.6%/4.19 MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Test data show that the compressive strength of concrete increases gradually when the content of NPOFA is as high as 30%. Ruan et al [125] and Han et al [126] found that the mechanical properties of RPC with NZ at a curing age of 28 days improve the compressive strength in comparison with plain RPC.…”
Section: Influence Of Other Nanomaterials On the Mechanicalmentioning
confidence: 99%
“…Test data show that the compressive strength of concrete increases gradually when the content of NPOFA is as high as 30%. Ruan et al [125] and Han et al [126] found that the mechanical properties of RPC with NZ at a curing age of 28 days improve the compressive strength in comparison with plain RPC.…”
Section: Influence Of Other Nanomaterials On the Mechanicalmentioning
confidence: 99%
“…Zirconium oxide nanoparticles have also been added in reactive powder concretes (RPC); several works showed that zirconium oxide nanoparticles do not accelerate the hydration process of RPCs, however, they can make the hydration products distribution more uniform, restricting the growth space of CH crystals, obtaining denser microstructures of these concretes. It has also been reported that high contents of zirconium oxide nanoparticles can contribute to better mechanical properties (up to 3% by weight), however, in the absence of a good dispersion, they can agglomerate and weaken the reinforcing effect [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…As the filler becomes smaller, it is surprisingly found that the addition of these tiny fillers can not only improve the mechanical properties and durability of cementitious materials but also endue them with such functionalities as electrical, thermal, and electromagnetic properties. 4 9 It is reported that the compressive strength of concrete can be increased up to 70% by incorporating nano-silicon dioxide particles. 10 The addition of 5% nano-aluminum oxide can enhance the elasticity modulus of cementitious composites up to 143%.…”
Section: Introductionmentioning
confidence: 99%